Associations between Reoperations and Psychological Factors after Contralateral Risk-Reducing Mastectomy: A Two-Year Follow-Up Study - Dmytro Unukovych; Marie Wickman; Kerstin Sandelin; Brita Arver; Hemming Johansson; Yvonne Brandberg (International Journal of Breast Cancer)
Introduction. The aim of the study was to investigate associations between reoperations after contralateral risk-reducing mastectomies (CRRM) and emotional problems, body image, sexuality, and health related quality of life (HRQoL) in women with breast cancer and hereditary high risk. Patients and Methods. Patients scheduled for CRRM with breast reconstruction between 1998 and 2010 completed questionnaires, comprised of SF-36, the Hospital Anxiety and Depression Scale, the Body Image Scale, and the Sexual Activity Questionnaire, preoperatively and two years after CRRM. Data on reoperations was collected from medical charts. Results. A total of 80 women participated, with a response rate of 61 (76%) preoperatively and 57 (71%) at the two-year follow-up. At the two-year assessment, 44 (55%) patients had undergone ≥1 reoperation (reoperation group), whereas 36 (45%) had not (no reoperation group). No statistically significant differences between the groups were found for HRQoL, sexuality, anxiety, or depression. A higher proportion of patients in the “reoperation group” reported being dissatisfied with their bodies (81% versus 48%, p=0.01). Conclusion. The results suggest associations between reoperation following CRRM with breast reconstruction and body image problems. Special attention should be paid to body image problems among women who are subject to reoperations after CRRM.